Vaccine design: methods and protocols: Volume 1: Vaccines for human diseases - Thomas, Sunil (Methods in molecular biology, 2016)
Clinical Impact of Vaccine Development -- Future Challenges for Vaccinologists -- Principles of Vaccination -- Reverse Vaccinology: The Pathway from Genomes and Epitope Predictions to Tailored Recombinant Vaccines -- Systems Vaccinology: Applications, Trends, and Perspectives -- Proteomic Monitoring of B Cell Immunity -- Development of Rabies Virus-Like Particles for Vaccine Applications: Production, Characterization and Protection Studies -- Analytic Vaccinology: Antibody-Driven Design of a Human Cytomegalovirus Subunit Vaccine -- Generation of a Single-Cycle Replicable Rift Valley Fever Vaccine -- Application of Droplet Digital PCR to Validate Rift Valley Fever Vaccines -- Methods to Evaluate Novel Hepatitis C Virus Vaccines -- Designing Efficacious Vesicular Stomatitis Virus-Vectored Vaccines against Ebola Virus -- Assessment of Functional Norovirus Antibody Responses by Blocking Assay in Mice -- Development of a SARS Coronavirus Vaccine from Recombinant Spike Protein plus Delta Inulin Adjuvant -- Generation and Characterization of a Chimeric Tick-Borne Encephalitis Virus Attenuated Strain ChinTBEV -- Single-Vector, Single-injection Recombinant Vesicular Stomatitis Virus Vaccines against High Containment Viruses -- Reverse Genetics Approaches to Control Arenavirus -- DNA Vaccines: A Strategy for Developing Novel Multivalent TB Vaccines -- Overcoming Enterotoxigenic Escherichia coli Pathogen Diversity: Translational Molecular Approaches to Inform Vaccine Design -- Design and Purification of Subunit Vaccines for Prevention of Clostridium difficile Infection -- The Design of a Clostridium difficile Carbohydrate-based Vaccine -- Murine Models of Bacteremia and Surgical Wound Infection for the Evaluation of Staphylococcus aureus Vaccine Candidates -- Using MHC Molecules to define a Chlamydia T Cell Vaccine -- An Approach to Identify and Characterize a Subunit Candidate Shigella Vaccine Antigen -- Approach to the Discovery, Development and Evaluation of a Novel Neisseria meningitidis Serogroup B Vaccine -- Anti-Lyme Subunit Vaccines: Design and Development of Peptide-based Vaccine Candidates -- Assessment of Live Plague Vaccine Candidates -- Highly Effective Soluble and Bacteriophage T4 Nanoparticle Plague Vaccines against Yersinia pestis -- Development of Structure-based Vaccines for Ehrlichiosis -- Dendritic Cell-based Vaccine against Fungal Infection -- Flow Cytometric Analysis of Protective T-cell Response against Pulmonary Coccidioides Infection -- High-Density Peptide Arrays for Malaria Vaccine Development -- Development and Assessment of Transgenic Rodent Parasites for the Pre-clinical Evaluation of Malaria Vaccines -- DNA Integration in Leishmania Genome: an Application for Vaccine Development and Drug Screening -- Methods to Evaluate the Preclinical Safety and Immunogenicity of Genetically Modified Live Attenuated Leishmania Parasite Vaccines -- The Use of Microwave Assisted Solid Phase Peptide Synthesis and Click Chemistry for the Synthesis of Vaccine Candidates against Hookworm Infection -- Methods and Protocols for Developing Prion Vaccines -- Ricin-Holotoxin Based Vaccines: Induction of Potent Ricin Neutralizing Antibodies -- Synthesis of Hapten-protein Conjugate Vaccines with Reproducible Hapten Densities -- Production of Rice Seed-based Allergy Vaccines -- Allergy Vaccines Using a Mycobacterium-Secreted Antigen, Ag85B, and an IL-4 Antagonist -- Development of House Dust Mite Vaccine -- Cancer Vaccines: A Brief Overview -- Dendritic Cell Vaccines -- Peptide-based Cancer Vaccine Strategies and Clinical Results -- Preconditioning Vaccine Sites for mRNA--Transfected Dendritic Cell Therapy and Antitumor Efficacy -- Development of Antibody based Vaccines Targeting the Tumor Vasculature.